Cerebral palsy understood as a physical disability, and on the use of assistive technology towards the inclusion of individuals - Mário Rui Cruz (Escola Superior de Educação de Paula Frassinetti, 2009)
In this article, we will focus on cerebral palsy understood as a physical disability, and on the use of assistive technology towards the inclusion of individuals with this disease. Based on a trial definition of this concept, we will try to make a conceptual analysis of cerebral palsy in this study, focusing our attention on the different associated types and issues and on the presentation of assistive technologies which would serve the purpose of promoting inclusion in the classroom and improving the living conditions of a learner diagnosed with this pathology. Thus, initially we will focus our attention on concepts, such as: communication systems, taking into account the perspective of the inclusion of students with communication difficulties in the classroom. Then we will present the plan of a natural activity in which a student with cerebral palsy will participate, engaging his/ her teachers and peers in reading and exploring the story f 'The Green Cricket', by Antonio Mota, which includes an approach to cultural diversity and a call for an intercultural approach. In this way, we will use the following assistive technology: a computer, an articulated arm, a pressure switch, Boardmaker ® with Speaking Dynamically Pro and even the BigMack device.